ON THE RECIPROCAL OF THE DIRICHLET-LAGRANGE THEOREM - Alva Morales, Gerard John (2016)
We study the instability in Lyapunov's sense of an equilibrium point of a Hamiltonian system with n degrees of freedom for a broad class of potential energies. We will show that this kind of potential energies determine sucient conditions for the instability of this equilibrium point.